Diversity-Oriented Synthesis of Natural Products via Gold-Catalyzed Cascade Reactions - Gu, Yueqing; Tan, Ceheng; Gong, Jianxian; Yang, Zhen (Synlett, 2018)
This account describes our group’s latest research in the field of diversity-oriented synthesis of natural products via gold-catalyzed cascade reactions. We present two general strategies based on gold-catalyzed cycloisomerization: a gold-catalyzed cascade reaction of 1,7-diynes and a pinacol-terminated gold-catalyzed cascade reaction. We highlight our development of synthetic methods for the construction of biologically active natural products by using these two strategies.1 Introduction2 Gold-Catalyzed Cascade Reactions of 1,7-Diynes2.1 Collective Synthesis of C15 Oxygenated Drimane-Type Sesquiterpenoids2.2 Synthesis of Left-Wing Fragment of Azadirachtin I2.3 Collective Synthesis of Cladiellins3 Pinacol-Terminated Gold-Catalyzed Cascade Reaction3.1 Asymmetric Formal Total Synthesis of (+)-Cortistatins3.2 Total Synthesis of Orientalol F3.3 Asymmetric Total Synthesis of (–)-Farnesiferol C4 Summary and Outlook
Keywords: gold catalysis; natural products; cascade reaction; total synthesis